Tissue engineering scaled-up, anatomically shaped osteochondral constructs for joint resurfacing - KELLY, DANIEL; BUCKLEY, CONOR; VINARDELL, TATIANA (My University, 2015)
Arthroplasty is currently the only surgical procedure available to restore joint function following articular cartilage and bone degeneration associated with diseases such as osteoarthritis (OA). A potential alternative to this procedure would be to tissue-engineer a biological implant and use it to replace the entire diseased joint. The objective of this study was therefore to tissue-engineer a scaled-up, anatomically shaped, osteochondral construct suitable for partial or total resurfacing of a diseased joint. To this end it was first demonstrated that a bone marrow derived mesenchymal stem cell seeded alginate hydrogel could support endochondral bone formation in vivo within the osseous component of an osteochondral construct, and furthermore, that a phenotypically stable layer of articular cartilage could be engineered over this bony tissue using a co-culture of chondrocytes and mesenchymal stem cells. Co-culture was found to enhance the in vitro development of the chondral phase of the engineered graft and to dramatically reduce its mineralisation in vivo. In the final part of the study, tissue-engineered grafts (~ 2 cm diameter) mimicking the geometry of medial femorotibial joint prostheses were generated using laser scanning and rapid prototyped moulds. After 8 weeks in vivo, a layer of cartilage remained on the surface of these scaled-up engineered implants, with evidence of mineralisation and bone development in the underlying osseous region of the graft. These findings open up the possibility of a tissueengineered treatment option for diseases such as OA
PUBLISHED
Export Date: 26 November 2015
Keywords: alginic acid; alginic acid